From Basic Biology to Patient Mutational Spectra of GATA2 Haploinsufficiencies: What Are the Mechanisms, Hurdles, and Prospects of Genome Editing for Treatment - Koyunlar, Cansu; de Pater, Emma (Frontiers in Genome Editing, 2020)
Inherited bone marrow failure syndromes (IBMFS) are monogenetic disorders that result in a reduction of mature blood cell formation and predisposition to leukemia. In children with myeloid leukemia the gene most often mutated is Gata binding protein 2 (GATA2) and 80% of patients with GATA2 mutations develop myeloid malignancy before the age of forty. Although GATA2 is established as one of the key regulators of embryonic and adult hematopoiesis, the mechanisms behind the leukemia predisposition in GATA2 haploinsufficiencies is ambiguous. The only curative treatment option currently available is allogeneic hematopoietic stem cell transplantation (allo-SCT). However, allo-SCT can only be applied at a relatively late stage of the disease as its applicability is compromised by treatment related morbidity and mortality (TRM). Alternatively, autologous-SCT (auto-SCT), which is associated with significantly less TRM, might become a treatment option if repaired hematopoietic stem cells would be available. Here we discuss the recent literature on leukemia predisposition syndromes caused by GATA2 mutations, current knowledge on the function of GATA2 in the hematopoietic system and advantages and pitfalls of potential treatment options provided by genome editing.